The Mediating Role of Brand Trust in The Influence of Celebrity Endorser Credibility on Purchase In-tention: A Study on Luxcrime Cosmetic Products in Denpasar - Syifa Pramitha Dewani; Ni Wayan Ekawati (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
The rapid growth of the Indonesian beauty industry has intensified competition among local brands, including Luxcrime, which faces challenges in increasing purchase intention. This study aims to examine the mediating role of brand trust in the relationship between celebrity endorser credibility and purchase intention among potential consumers of Luxcrime in Denpasar. The research applies the Stimulus-Organism-Response (SOR) theory as the theoretical foundation. A quantitative approach was used with purposive sampling, involving 110 respondents who had never purchased Luxcrime products. Data were collected through questionnaires and analyzed using path analysis and the Sobel test for mediation. The findings show that celebrity endorser credibility has a significant positive effect on purchase intention, both directly and indirectly through brand trust. Furthermore, brand trust significantly mediates the effect of celebrity endorser credibility on purchase intention. These results suggest that credible public figures not only directly influence consumers’ buying intentions but also strengthen brand trust, which in turn increases purchase intention. This study contributes theoretically to the understanding of the SOR framework in beauty marketing and offers practical insights for cosmetic brands in leveraging credible celebrity endorsements to build consumer trust and drive purchase decisions.